2017
DOI: 10.1007/s00535-017-1391-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of glecaprevir/pibrentasvir in Japanese patients with chronic genotype 1 hepatitis C virus infection with and without cirrhosis

Abstract: BackgroundThe once-daily, all oral, RBV-free, pangenotypic direct-acting anti-viral regimen consisting of co-formulated NS3/4A protease inhibitor glecaprevir and NS5A inhibitor pibrentasvir (G/P), demonstrated high rates of sustained virologic response (SVR) in phase 2 and 3 studies outside Japan.MethodsCERTAIN-1 is a phase 3, open-label, multicenter study assessing the safety and efficacy of G/P (300/120 mg) once daily in Japanese patients with chronic HCV GT1 infection. Patients without cirrhosis received 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 109 publications
(122 citation statements)
references
References 16 publications
3
115
0
Order By: Relevance
“…Considering the metabolism and excretion of these DAAs, it is presumed that they can be administered to patients with CKD. A phase 3 trial of glecaprevir/pibrentasvir demonstrated the high efficacy and safety in patients with CKD and those undergoing hemodialysis . IFN/ribavirin‐free, glecaprevir/pibrentasvir for pan‐genotype chronic hepatitis C patients is expected to treat genotype 2–6 chronic hepatitis C patients with CKD including hemodialysis, with high efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the metabolism and excretion of these DAAs, it is presumed that they can be administered to patients with CKD. A phase 3 trial of glecaprevir/pibrentasvir demonstrated the high efficacy and safety in patients with CKD and those undergoing hemodialysis . IFN/ribavirin‐free, glecaprevir/pibrentasvir for pan‐genotype chronic hepatitis C patients is expected to treat genotype 2–6 chronic hepatitis C patients with CKD including hemodialysis, with high efficacy and safety.…”
Section: Discussionmentioning
confidence: 99%
“…Eight weeks of the daily fixed‐dose combination of glecaprevir (300 mg)/pibrentasvir (120 mg) gained FDA approval for use in treatment‐naive or interferon‐experienced adolescents aged ≥ 12 years or weighing ≥ 45 kg with any HCV genotype infection, without cirrhosis or with compensated cirrhosis (Child‐Pugh A). Although the registration trial included only adolescents with genotype 1‐4, glecaprevir/pibrentasvir garnered FDA approval for all genotypes based on the safety and efficacy of the regimen demonstrated in adults . The recommendations for use of glecaprevir/pibrentasvir in treatment‐experienced adolescents are also based on clinical trial data from adults .…”
Section: Hcv In the Pediatric Populationmentioning
confidence: 99%
“…Subsequently, sofosbuvir plus ledipasvir (SOF + LDV), ombitasvir, paritaprevir plus ritonavir (OMV + PTV + r), and elbasvir plus grazoprevir (EBV + GPV), DCV + ASV plus beclabuvir therapies, and sofosbuvir plus ribavirin (SOF + RBV), OMV + PTV +r plus RBV, SOF + LDV therapies have become available for clinical use for genotypes 1 and 2 HCV‐infected patients, respectively. In 2017, the combination therapy with the NS3/4A inhibitor glecaprevir and the NS5A inhibitor pibrentasvir was approved for the pan‐genotypic treatment of HCV‐infected patients . Although the antiviral effect was drastically improved by the introduction of these DAA therapies, a small minority of patients remains unable to achieve viral eradication.…”
Section: Introductionmentioning
confidence: 99%